Assessment of Wind Energy Potential and Selection of Wind Park Location on the Example of the Trusina Mountain Ridge (Republic of Srpska, Bosnia and Herzegovina) - Milovanović, Zdravko; Branković, Dejan; Janičić-Milovanović, Valentina (Journal of Graphic Era University, 2024)
By signing international declarations and conventions, Bosnia and Herzegovina undertook to promote the production of energy from renewable sources, including wind energy. Designing a wind turbine system at a location requires knowledge of information about wind characteristics and resources, including information about turbulence. A wind energy potential estimates contain a high degree of uncertainty. Using wind data, including the average wind speed, an estimate of resources and possible electricity production is defined, as well as a location specification for one or more turbines. The successful development and location of wind parks depends on the accuracy of the assessment. The end result is a defined possible number of wind turbines on the site and a proposal for their arrangement with micro locations for each of the wind turbines of the future wind park. Within this paper, an example of the analysis of the Trusina wind park, located on the mountain ridge of the same name on the border of the local communities of Nevesinje and Berkovići, Republic of Srpska – Bosnia and Herzegovina, is given. The measurement campaign and a more detailed analysis of the collected data from all measurement stations in Bosnia and Herzegovina will be of great importance and will serve in determining the most favorable locations for the installation of production capacities based on wind energy. The conducted analysis of wind potential on the example of the Trusina mountain ridge represents a small contribution to solving this issue.